Investigation on structural and tribological properties of borided gear steel after phase homogenization - OK, ALAADDİN CEM (ELSEVIER SCIENCE SA, 2022)
This study focused on the structural and mechanical characterizations of AISI 8620 gear steel after a novel combined treatment (CRTD-Bor: Cathodic Reduction and Thermal Diffusion based boriding and subsequent PH: phase homogenization). Initially the effects of CRTD-Bor process parameters on the modified layer depth and chemistry were investigated at two sets of experiments as follows i) temperature examinations-15 min of CRTDBor at 950, 1000, 1050 and 1100 degrees C ii) duration investigations - at 950 degrees C for 15, 30, 60 and 120 min of CRTDbor. After that, PH treatment was integrated into CRTD-Bor to obtain industrially-desired monolithic Fe2B coatings. The optimized parameter of the dual treatment was found as 15 min of CRTD-Bor and subsequently 45 min of PH at 1000 degrees C, which resulted in 100 mu m thick sole Fe2B layer having 1600 +/- 100 HV hardness along with the perfect adhesion-HF1 quality. The tribological properties were evaluated by sliding wear tests in pin-on-disc configuration under dry and lubricated conditions. Since the wear in gear systems is of concern, wear tests were conducted to unborided pin/unborided disc, borided pin/unborided disc and borided pin/borided disc tribocouples. For both environments, the unborided tribo-pairs exhibited the highest loss whereas the borided tribo-couples had no measurable wear. Results of tribological tests revealed that the combined treatment successfully improved the wear resistance of the gears working in relative motions.
Keywords: Boriding; CRTD-Bor; Fe2B; AISI 8620; Gear steel; Wear; Phase homogenization; ABRASIVE WEAR BEHAVIOR; AISI 8620 STEEL; KINETICS; LAYERS; EVOLUTION; HARDNESS; GROWTH; CARBON